MORPHOMETRIC, MERISTIC, AND GROWTH PATTERNS OF BAUNG FISH (Hemibagrus nemurus C. V, 1840) FROM THE KAMPAR AND SIAK RIVERS, RIAU - Amelia, Helen; Efawani, Efawani; Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTHemibagrus nemurus is a type of freshwater fish that inhabit the Kampar River that has relatively good water quality and in the Siak River that has been polluted. As water quality affects the health status in general, the morphometric, meristic and growth pattern of H. nemurus living in those river might be different. To understand the morphometric, meristic and growth pattern of this fish, a study has been conducted on April-June 2018. There were 63 fishes (114.65-340 mm TL and 13.56–279.93 g W) from the Kampar River and 54 fishes (154.37-320 mm TL and 32.12–222.76 g BW) from the Siak River. The were 29 characteristics measured and 6 meristical characteristics counted. The meristical characteristics were as follows: D. I.7, P. I.6, V.6, A.10-11, C.20-22. In general, there was almost no significant different in morphological characteristics of fish from both sampling area, but the fish from the Kampar River shown that their body was wider than that of the Siak’s fish. The length-weight relationship of H. nemurus from both sampling sites were b= 3.2 (positive allometric, Kampar River) and b = 2.4 (negative allometric, Siak River).Keywords: Catfish, Morphological Characteristics, Meristical Characteristic, Growth Patterns.